2004
DOI: 10.1073/pnas.0404132101
|View full text |Cite
|
Sign up to set email alerts
|

TIFA activates IκB kinase (IKK) by promoting oligomerization and ubiquitination of TRAF6

Abstract: TRAF6 (tumor necrosis factor receptor-associated factor 6) is a RING (really interesting new gene) domain ubiquitin (Ub) ligase that mediates the activation of protein kinases, such as transforming growth factor ␤-activated kinase (TAK1) and IB kinase (IKK), by catalyzing the formation of a unique polyubiquitin chain linked through Lys-63 of Ub. Here, we present evidence that TIFA (TRAFinteracting protein with a forkhead-associated domain, also known as T2BP) activates IKK by promoting the oligomerization and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
114
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(119 citation statements)
references
References 27 publications
5
114
0
Order By: Relevance
“…Tubulin is used as a loading control. may facilitate TRAF6 stimulation of downstream pathways through oligomerization, similar to what has been shown for the TRAF6 interactor TIFA (45). In agreement with these results, we found that in the absence of NRIF, p75 was unable to activate the kinase (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Tubulin is used as a loading control. may facilitate TRAF6 stimulation of downstream pathways through oligomerization, similar to what has been shown for the TRAF6 interactor TIFA (45). In agreement with these results, we found that in the absence of NRIF, p75 was unable to activate the kinase (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…79 Activation of IKK involves the TRAFinteracting protein with a forkhead-associated (FHA) domain (TIFA) protein. 80 TIFA promotes the oligomerization of TRAF6 and enhances the autoubiquitinating activity of TRAF6, thereby facilitating downstream activation of NF-kB and JNK. 80 Activation of the IKKs leads to downstream phosphorylation of members of the inhibitor of NF-kB (IkB) family, resulting in ubiquitin-directed proteasome-mediated degradation of the IkB members, thus permitting the release and nuclear translocation of the transcription factor, NF-kB.…”
Section: Myd88-dependent Signalingmentioning
confidence: 99%
“…80 TIFA promotes the oligomerization of TRAF6 and enhances the autoubiquitinating activity of TRAF6, thereby facilitating downstream activation of NF-kB and JNK. 80 Activation of the IKKs leads to downstream phosphorylation of members of the inhibitor of NF-kB (IkB) family, resulting in ubiquitin-directed proteasome-mediated degradation of the IkB members, thus permitting the release and nuclear translocation of the transcription factor, NF-kB. 81 In endothelial cells, degradation of the IkB protein is dependent on its tyrosine phosphorylation and is specific to the IkBa isoform, while IkBb and IkBg protein levels remain unchanged following LPS stimulation.…”
Section: Myd88-dependent Signalingmentioning
confidence: 99%
“…A role for oligomerization of TRAF6 in enhancing its ubiquitinating activity has also been postulated [39,42,43]. In fact, TRAF-interacting protein with a forkhead-associated domain (TIFA) was found to interact with TRAF6, thereby inducing TRAF6 oligomerization and enhancing TRAF6 ubiquitinating activity [50]. Endogenous TIFA constitutively associates with TRAF6, whereas it only interacts with IRAK-1 upon IL-1 stimulation [51].…”
Section: Il-1r and Tlr-4 Signaling To Nf-kbmentioning
confidence: 99%